(untitled) (Collection of scientific works «Modern structures of metal and wood», 2025)
Compared to traditional building materials and techniques, the use of prefabricated modular structures has the potential to solve the problems of environmental impacts such as energy consumption and the associated carbon dioxide emissions. The use of materials with a high potential for recycling and reuse, such as steel in the form of rolled or cold formed profiles, is fully in line with the principles of the circular economy - a shift from a linear to a circular material use. Unlike rolled profiles with open and closed cross-sections made of structural steels, which use intumescent paints for fire protection, cold-formed steel profiles, due to their relatively small thickness, require the use of fireproof coatings of greater thickness (10-15 mm) based on gypsum or perlite. For galvanized profiles, the only fire protection method available is cladding using various types of fireboards. The investigation of steel volumetric modules design economic factors influenced by different methods of fire protection were conducted at the Department of Metal, Wooden and Plastic Structures. Further investigation of economical design related factors of fire resistance of cold formed structures of volumetric modular construction intended to fill the gap. The research is focused on the performance of cold formed steel bearing structures, as well as fire resistance of cold formed steel profiles and fire protection methods.